2020
DOI: 10.1038/s41598-020-64115-z
|View full text |Cite|
|
Sign up to set email alerts
|

Crystal structure of Type IX secretion system PorE C-terminal domain from Porphyromonas gingivalis in complex with a peptidoglycan fragment

Abstract: Porphyromonas gingivalis, the major human pathogen associated to periodontal diseases, utilizes the Bacteroidetes-specific type IX secretion system (T9SS) to export virulence factors. PorE is a periplasmic multi-domain lipoprotein associated to the outer membrane that was recently identified as essential for T9SS function. Little is known on T9SS at the structural level, and in particular its interaction with peptidoglycan. This prompted us to carry out structural studies on PorE full length as well as on its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Proteins that carry this role in the context of other periplasmic complexes have been identified and characterized. In particular, a multitude of PG‐binding proteins with an OmpA‐like motif or a LysM motif have been associated to flagellar systems, Type 4 pilus, Type 2, Type 6, and Type 9 secretions systems [57–64], while other PG‐binding motifs have been associated with Type 3 secretions systems [65]. These nonhydrolytic enzymes direct the assembly of the macromolecular secretion complexes at specific spatial or temporal points within the PG layer [66] and participate in the stabilization of these complexes to promote their function at the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins that carry this role in the context of other periplasmic complexes have been identified and characterized. In particular, a multitude of PG‐binding proteins with an OmpA‐like motif or a LysM motif have been associated to flagellar systems, Type 4 pilus, Type 2, Type 6, and Type 9 secretions systems [57–64], while other PG‐binding motifs have been associated with Type 3 secretions systems [65]. These nonhydrolytic enzymes direct the assembly of the macromolecular secretion complexes at specific spatial or temporal points within the PG layer [66] and participate in the stabilization of these complexes to promote their function at the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…Its sequence analysis revealed that it is a lipoprotein and is composed of four domains: a tetratricopeptide repeat domain; a five-bladed beta-propeller domain; a predicted carboxypeptidase regulatory domain-like fold, and an OmpA_C-like domain [ 22 ]. A crystal structure of the OmpA_C-like domain bound to the peptidoglycan was solved recently [ 42 ]. This domain (residues 534 to 668) was expressed and purified from E. coli .…”
Section: Structurementioning
confidence: 99%
“…This domain (residues 534 to 668) was expressed and purified from E. coli . The solved structure was a tetramer; however, the oligomerization was perhaps an artefact of crystallization as size exclusion chromatography, and multi-angle light scattering analysis indicated that the protein was stable in a monomeric form in solution [ 42 ]. The structure consists of a three-stranded beta-sheet and five alpha-helices with the connectivity of α1β1α2β2α3α4α5β3.…”
Section: Structurementioning
confidence: 99%
“…Other secretion systems spanning both the outer and inner membranes comprise also a component harbouring a PGDB. ExA from the Aeromona hydrophila T2SS was shown to cross-link with PG [ 34 ], and recently, the structure of the PorE PGBD from the Porphyromonas gingivalis T9SS was solved in complex with a PG fragment [ 35 ]. In many T6SSs, the PGBD is fused to the C terminus of TssL, which are then called “specialized TssL”.…”
Section: Introductionmentioning
confidence: 99%